Analysing varying rate flood attack on real flow in MANET and solution proposal 'real flow dynamic queue'. (2017) - Verma, Sourabh Singh; Patel, R.B.; Lenka, Saroj Kumar
Mobile ad-hoc networks (MANET) are vulnerable to various types of attacks, which can hinder the performance of network. In this paper, we have projected in what way request flooding effects on the performance of real data flow considering nodes flooding with variable flooding rates, while real flow have stringent requirements. We also proposed a solution named 'real flow dynamic queue (RFDQ)' which is evaluated against priority queue in ns2 with extensive evaluation and results. It is noticed in result that RFDQ works better for real data flows under flooding attack. Our intent is to show varying rate flooding has severe impact on real data flows by considering different parameters and how RFDQ can be a better replacement over priority queue.